Too many toys - Shannon, David, 1959- (New York : Blue Sky Press, 2008)
Although he finally agrees that he has too many toys and needs to give them away, there is one toy that Spencer absolutely cannot part with.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Keywords: Toys -- Juvenile fiction; Parent and child -- Juvenile fiction; Toys -- Fiction; Parent and child -- Fiction